Circulation of the discourse of American nationalism through allegiance to consumer citizenship in Jhumpa Lahiri’s The Namesake - Asl, Moussa Pourya; Nurul Farhana Low Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2017)
This essay examines South Asian American writer Jhumpa Lahiri’s literary engagement with the re-Orientalization and sexualization of a collective subject described as Indian diaspora within the context of contemporary consumer culture. The essay explores the relationship between Lahiri’s best-selling novel, The Namesake (2003) and its contemporary society by taking the point of view that diasporic literary writing is an example of a Foucauldian social apparatus—a new form of governmentality—that was used for the production of American nationalism after the events of 9/11. Here, we expose the material and ideological specificities that formulate a particular group of women as powerless consumers in the context of the post-cold war period. More precisely, we focus on the ideological elements of the routine consuming experiences of these women to unpack the manner in which the macropolitics of economic and political structures influence the micropolitics of the everyday experiences of Indian immigrants in the capitalist society. In Lahiri’s fiction, the Indian woman’s body—in its both first- and second- generation types—is figured as a deliberate site of economic and erotic excess that fundamentally complies with the contemporary heteronormative ideology of patriarchal capitalism, wherein the woman is essentially treated as the archetypal consumer. In effect, as the essay further argues, Lahiri’s fiction dances to the tune of Western marketing demands of production and consumption.